Ethical Hacking and Penetration Testing in Financial Services - Ajay Benadict Antony Raju (North American Journal of Engineering Research, 2022)
In aspects relating to the business of financial services, this has raised special, unique risks created by the use of digitaltechnologies, hence the need for extra measures to secure the ever-growing valuable financial information used within thissector to prevent it from being attacked by hackers. Ethical hacking and penetration testing have therefore grown to be essentialactivities to highlighting security risks that may be exploited by the malicious parties. Ethical hacking involves the legitimatesecurity personnel conducting a mimic attack against a system with an intention of identifying its vulnerabilities whilepenetration testing involves emulating an actual attack on the current security measures in place. In the financial sector, wherethere are large risks due to the sensitivity of the personal and financial information these measures are essential. In this paper,the author analyses the nature of ethical hacking and penetration testing as a way to improve the cybersecurity level in thefinance organizations and mentions how it can help organizations defend against new threats, meet the requirements oflegislation and maintain the security on a constant level